A Studi Sistem Struktur Baja Diagrid Pada Bangunan Tinggi - Draga Hasan saputra Saputra; Pio Ranap Tua Naibaho (Jurnal Infrastruktur, 2019)
Diagrid also known as diagonalized grid structure have emerged as one of the most innovative and adaptable approaches and have evolved to the point of making its use non-exclusive to tall buildings. The advantage of this system thus even outweight the disadvantages which are specifically the complexity in design, joint connection construction and the high cost of the structure. Therefore studies related to a structure of this kind which has a huge scope in the future are highly desirable. Analysis using linear dynamics of various structures has been carried out in ETABS using the spectrum response method. The analysis results in term of the top storey displacement, inter-storey drift and time period have been compared to understand the diagrid structure system. The first comparison between diagrid and conventional system has been analysed to illustrate the superiorty of the diagrid system. This comparison illustrate the importance of diagrid in reducing various lateral load parameter such as top storey displacement, inter-storey displacement and time period. The value of the top storey displacement for conventional systems in the direction of x dan y is 34,2% and 30.9% higher than the diagrid system. Both system comparison are hybridized with and without shear wall cores. From the results of the shear wall core effect in the diagrid system, it was observed that the shear wall core improved the performance of the diagrid structure. Lateral top storey displacement decreases from 48.2 mm to 43.5 mm so it is reduced by 10%.